In Vitro Effects of St. John’s Wort Extract Against Inflammatory and Oxidative Stress and in the Phagocytic and Migratory Activity of Mouse SIM-A9 Microglia - Bonaterra, Gabriel A.; Mierau, Olga; Hofmann, Johanna; Schwarzbach, Hans; Aziz-Kalbhenn, Heba; Kolb, Christiane; Kinscherf, Ralf (Frontiers in Pharmacology, 2020)
Introduction: Herbal medicinal plants as Hypericum perforatum L., known as St. John's wort (SJW) have been in use for a long time. SJW that is specifically used for the treatment of depressive disorders. Inflammatory cytokines derived from microglia play an important role in the regulation of the synthesis and reuptake of glutamate and influence synaptic function, morphology and neuronal plasticity. The present study was performed to investigate, whether STW3-VI, a special SJW extract has protective effects on mouse SIM-A9 microglia against cytotoxic and proinflammatory effects of ROS, glutamate, NMDA or cortisol. Additionally, we investigated the effects of SJW on migratory and phagocytic properties of microglia. Results: Pre-treatment (48h) of microglia with STW3-VI (5 or 10 µg/ml) – in contrast to desipramine – inhibited the H2O2-induced TNF-α release by 20%-40%. Pre-treatment (48h) of microglia with STW3-VI (5 or 10 µg/ml) delayed the 3 or 4 mM H2O2-induced intracellular ROS level by 26.9% and 44.4%, respectively. Furthermore, pre-treatment (48h) of microglia with STW3-VI (5 µg/ml) - in contrast to desipramine - lowered the glutamate-induced cytotoxicity by 13.2%. Besides, pre-treatment (48h) of microglia with STW3-VI (5 or 10 µg/ml) or desipramine (5 µM) inhibited the NMDA-induced decrease of the viability by 16.5%-28.8% or 12%, respectively. Finally, pre-treatment (48h) of microglia with STW3-VI (5 or 10 µg/ml) – in contrast to desipramine - reduced the cortisol-induced cytotoxicity by 15.5% and 12.9%. Treatment of microglia with STW3-VI (10 or 100 µg/ml) increased the migratory and the phagocytic capacities by 100% and 40%. Conclusions: Our data provide evidence that STW3-VI – in contrast to desipramine - protects microglia from oxidative stress, NMDA- or glutamate-induced cytotoxicity, and has anti-inflammatory properties that are accompanied by improvement of their migratory and phagocytic capacity. These protective (particularly the anti-inflammatory) properties may be beneficial in the treatment of depressive disorders.